Distribusi Unsur Hara N dan P dalam Sedimen di Ekosistem Lamun (Seagrass) di Wilayah Pesisir Desa Kabonga Besar Kabupaten Donggala - Silvia, Mega; Tiwow, Vanny M.A.; Said, Irwan (Universitas Tadulako, 2014)
This research aims to determine the distribution patterns and concentrations of nitrogen and phosphorus nutrients in the sediment at the coastal region of seagrass ecosystems Kabonga Besar village Donggala district. Phosphorus (P) and nitrogen (N) in water its are nutrient that is essential for the growth of phytoplankton. This research was carried out by quantitative analysis using a nitrogen compound Kjeldhal method which consists of three phases: destruction, distillation, and titration, while for phosphorus compound using UV-Vis spectrophotometric method. The results showed that the lowest levels of nitrogen were obtained at the level of fertility sea grass sediments are less abundant range of 0.05% - 0.06% , on the contrary sea grass abundant fertility rate which ranges from 0.07% - 0.09%. For the highest levels of phosphorus nutrients contained in the water that is abundant on sea grass fertility ranged from 4.335 - 4.387 mg/100, and the lowest was ranged from 2.292 - 2.358 mg/100. Based on the data obtained it can be concluded that the content of nitrogen and phosphorus nutrients in sediments sea grass at the research area was still relatively low, it could affect the growth of seagrass.